How top executives’ ‘academic experience’ and ‘political connection’ affect corporate innovation? - BAI, SHA (2020)
In the fierce market competition, talents and technology have become the core competence of enterprises. Many professors and researchers in scientific research institutions have left schools and laboratories to work in companies or start their businesses. When they join the company’s top management team (TMT), ‘academic experience’ will affect company performance. In addition, executives with a political background also have an impact on the development of the corporate. This paper uses a sample of 99 Chinese high-tech firms from 2014 to 2017 to investigate how executives with these backgrounds affect corporate innovation. The results indicate that executives’ ‘academic experience’ will enhance corporate innovation. When the proportion of academic executives in the top management team (TMT) increases, the team tends to make decisions that promote corporate innovation. On the contrary, executives’ ‘political connection’ fails to strengthen corporate innovation. When the proportion of executives with ‘political connection’ in the TMT increases, the team might make strategies that are not conducive to corporate innovation.